THE METHODS OF CONSTRUCTION OF SYSTEMS OF CONTROL OF HYDROLITHOSPHERE PROCESSES - G. E. Veselov; M. I. Pershin (Современная наука и инновации, 2022)
The paper discusses methods of constructing control systems hydrolithosphere processes. The methodology and main stages of synthesis of distributed systems management is considered on the example of construction of a control system hydrolithosphere processes of Kislovodsk mineral water. Input effects on the object of management is the production rate wells. As a function of the selected output level drawdown in the vicinity of the location of the production well.